Dose-response relationship of egg consumption with cognitive function in rural older adults: a large-scale population-based study - Ren, Tingyun; Yuchi, Yinghao; Feng, Lange; Wang, Xinlai; Liao, Wei; Tian, Zhenzhen; Zhang, Huanxiang; Tian, Yuan; Li, Yuqian; Wang, Chongjian (Frontiers in Nutrition, 2025)
BackgroundPrevious studies had accessed the effect of egg consumption on cognitive function, but the general population-based evidence is limited and inconclusive. In addition, the optimal intake of egg remains unclear. The study aimed to investigate the association of egg consumption with mild cognitive impairment (MCI) in rural adults and then explore the recommended intake of eggs.MethodsThis study included 14,550 participants from the second wave of the Henan Rural Cohort Study. Egg consumption was assessed using a validated food frequency questionnaire. Cognitive function was measured using the Mini-Mental State Examination (MMSE). MCI was defined as MMSE scores ≤ 17 for illiteracy, ≤ 20 for primary school education, or ≤ 24 for junior high school education or higher. Logistic regression analyzed the relationship between egg intake and MCI. Dose-response relationships were evaluated using restricted cubic spline (RCS) models.ResultsThe adjusted odds ratio (OR) and 95% confidence interval (CI) of per SD increase of daily egg consumption for MCI was 0.925 (0.891, 0.960). A U-shape dose-response relationship between egg consumption and MCI was found (p < 0.001), and the optimal egg intake was 87.94 g/day. The further analysis showed that OR (95%CI) per SD increase of egg consumption below and above the optimal intake (87.94 g/day) was 0.826 (0.774, 0.880) and 1.188 (1.056, 1.336), respectively. Sensitivity analyses showed similar results.ConclusionEgg consumption is associated with cognitive function among rural populations and eat egg 87.94 g/day could have best benefit, supporting its potential role in dietary strategies for cognitive health.